THE DEVELOPMENT OF A MANAGER’S LEADERSHIP QUALITIES AS A PEDAGOGICAL ISSUE - Sergeeva, Marina; Simonova, Natalia; Oreshkina, Anna; Lukashenko, Dmitry; Egorova, Liudmila (Revista Inclusiones, 2020)
The issue of leadership has always raised interest among scientists and ordinary company staff. In connection with the global changes of the late 20th and early 21st centuries, the demand for leadership as a personal ability to unite people in order to reach goals rose dramatically. It is especially true for the manufacturing management, whose main purpose is in a rational management for the sake of maximal revenue. We can state that in modern conditions, there is an urgent need of companies in the development of leadership qualities and leadership behavior. Depending on the company goals, the sphere of its activity and on the situation inside and outside the company, the activity at similar management positions will significantly vary. In some key points, the requirements to the manager’s knowledge, skills and personal qualities, as well as to managerial methods and tasks, will be different. Much depends on such situational factors as the level of the group development, its members’ expectations, and task specifics. Alongside this, the universal significance of such leadership qualities as independence, initiative, adaptivity and motivation rises. It seems relevant to study such a phenomenon of a manager’s “leadership qualities” as a complex social and psychological phenomenon which combines individual and group factors that ensure a successful achievement of joint goals. The modern society needs specialists who can not only prove their professional skills and competence, but also show positive personal characteristics facilitating the development of their professional and social activity.